Perlindungan Hukum terhadap Trading Online yang Dilakukan oleh Generasi Z dalam Perspektif Hukum Pasar Modal di Indonesia (Lex Mercatoria, 2025)
This article provides an in-depth examination of legal protection for Generation Z investors engaging in online trading activities within the Indonesian capital market. The rapid expansion of digital trading platforms has significantly increased the participation of young retail investors, while simultaneously intensifying legal risks related to information asymmetry, investor vulnerability, and regulatory compliance. Employing a normative legal research method, this study applies statutory, conceptual, and analytical approaches to assess the adequacy and effectiveness of Indonesia’s capital market regulatory framework in responding to these challenges. The analysis is grounded in the provisions of Law Number 8 of 1995 on Capital Markets, Law Number 21 of 2011 on the Financial Services Authority, and relevant implementing regulations governing online trading activities. The study identifies three principal findings. First, legal protection for online trading investors is normatively available through disclosure obligations, licensing requirements, and supervisory mechanisms implemented by regulatory authorities. Second, despite the existence of comprehensive regulations, Generation Z investors remain legally vulnerable due to limited legal literacy, inadequate understanding of investment risks, and overreliance on digital platforms. Third, the current legal framework requires stronger adaptive supervision and targeted legal education to effectively address the unique characteristics of Generation Z as technology-driven retail investors. This article contributes to capital market legal discourse by emphasizing the need to harmonize regulatory protection, technological development, and investor awareness in the digital trading ecosystem.Keywords: Legal Protection, Online Trading, Generation Z, Capital Market Law, Retail Investors